(untitled) (Scientific journal of the Fergana State University, 2024)
This article aims to explore the pedagogical strategies for teaching patriotism and friendship through Uzbek folk tales. By examining existing research, analyzing the cultural and educational significance of Uzbek folk tales, and exploring effective instructional practices, this study seeks to provide educators with practical insights and recommendations. Through the integration of Uzbek folk tales into teaching practices, educators can foster a deeper understanding of patriotism, cultivate strong friendships, and promote a sense of unity and respect among students.